Clinico-Pathological Correlations of the Most Common Neurodegenerative Dementias - Taipa, Ricardo; Pinho, João; Melo-Pires, Manuel (Frontiers in Neurology, 2012)
Neurodegenerative dementias are a group of neurological disorders characterized by deterioration in several cognitive domains in which there is selective and progressive loss of specific populations of neurons. The precise neurobiological basis for the different neurodegenerative dementias remains unknown. It is expected that different pathologies reflect different mechanisms, at least early in the neurodegeneration process. The next decades promise treatments directed to causes and mechanisms, bringing an outstanding challenge to clinicians due to heterogeneous clinical presentations with the same molecular pathology. The purpose of this brief review is to describe the key neuropathological features of the most common neurodegenerative dementias (Alzheimer disease, dementia with Lewy bodies and Parkinson’s disease dementia, and frontotemporal lobar degeneration) and the relationship with the clinical syndromes described in clinico-pathological studies. We expect this overview contributes for the understanding of this broad topic integrating the two ends of the spectrum: clinical and pathological.